PEMERINTAH DI HADAPAN KORPORATISME MULTINASIONAL : KASUS EKSPLORASI DI FREEPORT, KPC (KALTIM PRIMA COAL) DAN BLOK CEPU - Mohammad Taufik (Jurnal Paradigma (JP), 2017)
The main purpose of this article is to explain the bargaining position of Indonesian government vis a vis Multinational Corporations particularly concerning with exploration of natural resources by Freeport, KPC and Cepu. In order to obtain the best understanding about the central issue of this article, the using of global economic and sovereignty concept are necessary. The analysis of this issue shows that foreign investment (MNCs) did not bring any advantages for increasing the quality of social life in Indonesia.